Warunek co do przyszłości (kan. 1102 § 1 KPK) w wyroku Roty Rzymskiej c. Alwan z dnia 18 kwietnia 2008 roku - Góralski, Wojciech (Ius Matrimoniale, 2018)
The rotal sentence c. Alwan, concerning marriage between Edmund and Emma, concluded on April 23, 1985, was passed. Marriage was not a happy one from the beginning and the wife, after serious misunderstandings and conflicts, definitely left home, taking a six-month-old child with her (July 3, 1986). On May 29, 1989 the man asked the Ecclesiastical Court in Radom to declare his marriage null and void on the basis of simulation of marriage consent by the woman. On September 25, 1990, a negative sentence was passed. On February 9, 1993, Edmund initiated a new case (in the same court) on the basis of de future condition made by him in relation to the defendant (that she would move to his family home to help his elderly parents on their farm), which she did not met. On January 28, 1995, a sentence declaring the marriage null and void was passed. It was revoked by the Court of Appeals in Częstochowa. The case was taken to the Roman Rota (in the third instance) where, on April 18, 2008, a positive sentence, declaring the marriage null and void, was passed. The author provides a commentary on the rotal sentence highlighting the thoroughness of auditors when assessing the condition which was not met by the defendant.